China-US Trade War and the Challenges for Developing Countries - Ahmad Anwar (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2026)
The US-China trade war signifies a fundamental shift in global economic governance, which has moved beyond a mere tariff dispute to redefine the nature of the strategic environment, particularly for developing countries. This research seeks to explore the vulnerabilities that the US-China trade war imposes on developing countries through three mechanisms: trade diversion that provides asymmetric opportunities based on adaptive capacities, intensification of alignment pressures that require developing countries to deal with competing regulations, and the securitization of their economic dependencies, which transforms supply chain participation into a geopolitical liability. Utilizing a process tracing methodology, this research seeks to analyze the sequences through which tariff escalations and technology restrictions spread across the world, thereby concentrating their dependencies and imposing a new dimension of vulnerability on developing countries. It argues that while developing countries benefit from the production relocation, their overall dependence on the rest of the world has increased, with integration happening within power-contested rather than market-driven frameworks. The US-China trade war, as this research seeks to demonstrate, signifies a structural shift in the nature of the relationship between economic integration and security, with far-reaching implications for developmental autonomy.